NIGERIAN CONSTRUCTION-RELATED PROFESSIONAL SERVICES FIRMS TO ADOPT LEAN CONSTRUCTION PRACTICES - Olajide Olamilokun; Umar Datti Yusuf; Emmanuel Dele Omopariola (Journal of Construction Project Management and Innovation)
Studies have shown that construction projects are susceptible to problems such as low productivity, poor safety, inferior working conditions, insufficient quality, lack of timely communication and coordination amongst project stakeholders, and rising litigation. Adoption of lean construction (LC) principles within the manufacturing industry and other industries has led to notable improvement and resulted in improved time to market, reduced production costs, improved quality of the product, and active customer involvement. The study assessed the readiness of Nigerian construction-related professional services firms to adopt LC principles. The method of study involved a critical exposition of related literature, and use of the VERDICT readiness assessment model for analysis, and an ANOVA for readiness comparison. A structured questionnaire was issued for a sample size comprising 130 firms drawn from a finite population of 342 Nigerian construction-related professional services firms (project managers, architects, quantity surveyors, structural engineers, and M&E engineers) operating in Northern Nigeria. The findings of the study reveal that Nigerian construction-related professional services firms have process/project readiness to adopt LC principles, but that they do not have management, people and technology readiness to adopt LC principles. The study concludes that Nigerian construction-related professional services firms are not yet ready to adopt LC principles. The study recommends continuous awareness campaigns of LC principles and their potential benefits, via education and training to professional bodies, tertiary institutions offering construction-related programmes, and stakeholders in the construction industry.